A VIABLE ENTREPRENEURSHIP EDUCATION AS AN ANTIDOTE FOR ERADICATION OF POVERTY AND UNEMPLOYMENT AMONG YOUTHS IN NIGERIA (Journal of Business Management and Accounting, 2022)
Nigeria is passing through a period of uncertainty and pervasive economic recession which has further aggravated the problem of poverty and unemployment among Nigerian youths. These jobless youths take solace in all form of atrocities and social vices that pose a serious threat to sustainable development of the nation. This research took a cursory look at the concepts of poverty, youth unemployment and viable entrepreneurship education. It highlighted the lofty objectives of viable entrepreneurship education in Nigeria. The various factors responsible for poverty and youth employment in Nigeria were identified. Attention was also directed to the role of viable entrepreneurship education in eradicating poverty and youth unemployment in Nigeria. Based on the findings, it was recommended, among others, that the curriculum of educational institutions in Nigeria should be more pragmatic and have built-in-job training programmes which would enable all students to acquire relevant entrepreneurial skills required for self-employment, job and wealth creation and poverty eradication.